2012
DOI: 10.1186/1465-9921-13-62
|View full text |Cite
|
Sign up to set email alerts
|

WNT7B in fibroblastic foci of idiopathic pulmonary fibrosis

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a devastating interstitial pneumonia causing a loss of respiratory surface area due to a proliferative fibrotic response involving hyperplastic, hypertrophic, and metaplastic epithelium, cystic honeycomb change, septal expansion, and variable inflammation. Wnt (wingless) signaling glycoproteins are known to be involved in lung development and tissue repair, and are up-regulated in patients with IPF. Based on previous qRT-PCR data showing increased Wnt7B in lungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 37 publications
5
47
0
Order By: Relevance
“…Although our findings argue against FGF2 specifically being required for bleomycininduced pulmonary fibrosis in mice, they do not argue against FGF signaling via any of the other 17 secreted FGF ligands. FGF9 expression, for example, is increased in areas of active fibrosis in IPF lungs, and is further enhanced by Tgfb1 and Wnt7B, which are coexpressed in these regions (48,49). Consistent with prior reports, we observed an increase in downstream FGF signaling in response to bleomycin (10).…”
Section: Fgf2 and Pulmonary Fibrosissupporting
confidence: 81%
“…Although our findings argue against FGF2 specifically being required for bleomycininduced pulmonary fibrosis in mice, they do not argue against FGF signaling via any of the other 17 secreted FGF ligands. FGF9 expression, for example, is increased in areas of active fibrosis in IPF lungs, and is further enhanced by Tgfb1 and Wnt7B, which are coexpressed in these regions (48,49). Consistent with prior reports, we observed an increase in downstream FGF signaling in response to bleomycin (10).…”
Section: Fgf2 and Pulmonary Fibrosissupporting
confidence: 81%
“…Wnt7B is known to be important during early lung development as a signaling glycopeptide that directs proliferation of adjacent epithelium and mesenchymal cells (Rajagopal et al 2008) and controls the growth of vasculature (Shu et al 2002). This has led to the suggestion that Wnt7B may be reactivated to significantly impact the progression of IPF in the adult lung (Morrisey 2003;Meuten et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β is probably best known for its regulatory influences on fibrogenesis in IPF (Chilosi et al 2003;Fernandez and Eickelberg 2012) by fostering the growth of myofibroblasts and the expansion of fibrillar collagen and various components of the ECM, which, in many cases, is cooperatively controlled by Wnt signaling (Broekelmann et al 1991;Scotton and Chambers 2007;Salazar, Lankford, and Brody 2009). Wnt7B gene expression has been reported to be upregulated in IPF lungs (Konigshoff et al 2008) and found to be localized in tissue sections within distinct sites that include cells and the ECM within FF of IPF lungs (Meuten et al 2012). Wnt7B is known to be important during early lung development as a signaling glycopeptide that directs proliferation of adjacent epithelium and mesenchymal cells (Rajagopal et al 2008) and controls the growth of vasculature (Shu et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations